Unveiling the mechanism of dodecylphosphorylcholine as an extremely promising drug delivery system: From self-assembly clusters to drug encapsulation pathways - Qijiang Shu; Linjing Yang; Li Li; Zedong Lin; Pengru Huang (PLoS ONE, 2025)
Significant progress has been achieved in cancer treatment with Doxorubicin (DOX), yet its low toxicity and poor bioavailability have long troubled scientists. Dodecylphosphorylcholine (DPC), as a candidate material for drug delivery systems (DDS), holds promise in assisting DOX to overcome its application bottleneck. In this study, employing a combination of quantum chemical calculations and molecular simulations, we delve into the dynamic processes of the interaction between DPC and DOX molecules for the first time. The results indicate that, under the synergistic effect where electrostatic repulsion plays a minor role and van der Waals attraction predominates, the end (containing choline group) of DPC molecules aggregate, self-assembling into multiple molecular clusters. There is a notable presence of electrostatic attraction and van der Waals attraction between DPC and DOX, which drives the adsorption or encapsulation of DOX molecules by DPC molecular clusters, thus presenting a favorable drug-loading conformation. During these processes, a substantial number of DPC molecules aggregate around DOX, with typical distances for interaction around 0.5 nm. The shape and position of DPC-DOX molecular clusters undergo significant dynamic changes within a simulated time of 0–70 ns, stabilizing thereafter. Our findings elucidate the interaction mechanism between DPC and DOX at the molecular scale, paving new avenues for the experimental synthesis of promising DDS eagerly sought by DOX.